Morphological and topographical characteristics of posterior supernumerary molar teeth: An epidemiological study on 25,186 subjects - Cassetta, M.; Altieri, F.; Giansanti, M.; Di-Giorgio, R.; Calasso, S. (Medicina oral, patología oral y cirugía bucal, 2014)
To investigate the prevalence , gender difference , arch , morphology and position within the arch of supernumerary molar (SM) teeth in a referred Italian Caucasian population. Records of 25,186 young patients were evaluated. Only data related to supernumerary teeth in the posterior region of the jaws were analyzed. The diagnosis of hyperdontia was formulated during the clinical and radiological examinations based on panoramic radiographs. Statistical analysis was conducted at level of subjects in the assessment of prevalence of SMs and sex ratio. Statistical analysis was conducted at level of teeth according to their morphological and topographic characteristics. The analysis of association between supernumerary morphology and arch, between supernumerary position and arch and between morphology and position was performed using the χ2 test (P≤ 0.05). 61 posterior supernumerary teeth were found in 45 patients. The male to female ratio was 2.5:1 ;the mean age was 21.23 (IC:95%).The SMs were found more frequently in the maxilla (62.3%) than in the mandible; supernumerary teeth (60.7%) were more frequent than supplemental teeth. The SMs were mostly of tuberculate shape (56.8%) and paramolars teeth (64.9%) were more common than distomolars. 54% of teeth were erupted in the arch. No statistically significant relationship were found between the supernumerary teeth shape and the arch (P= 0.087) , between supernumerary teeth position and the arch (P=0.511) and between morphology and position (P=0.216). Epidemiological studies related to supernumerary teeth can be useful to clinicians in the early diagnosis of this anomaly. In this retrospective study the prevalence of SMs was 0.18%. SMs were more frequent in males and in the maxilla. Supernumerary were more frequent than supplemental; the conical morphology and paramolar position were the most common shape and position.